PENGARUH METODE PEMBELAJARAN TEAM GAMES TOURNAMENT DAN QUANTUM TERHADAP PRESTASI BELAJAR IPS DITINJAU DARI KEMAMPUAN AWAL SISWASD NEGERI KECAMATAN PARANGGUPITO - Rusmanto, Sugeng (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The objectives of this research are to investigate: (1) whether or not there is a difference of effect between the team games tournament learning method and the quantum learning method on the learning achievement in Social Science; (2) whether or not there is a difference of effect between the studentsâ high initial ability and the studentsâ low initial ability on the learning achievement in Social Science; and (3) whether or not there is an interaction effect between the learning methods and the studentsâ initial abilities on the learning achievement in Social Science.This research used the quantitative research method with the experimental method. It was conducted at State Primary School 2 of Ketos as experimental class and State Primary School 1 of Paranggupito as control class. The former and the latter were treated with the team games tournament and the quantum learning method.Â  The population of the research included all of the students of State Primary Schools in ParanggupitoÂ  sub-district, Wonogiri regency. The samples of the research were taken by using the purposive random sampling technique.Â  The data of the research were analyzed by using the two-way analysis of variance with the pre-requisite tests of normality test and homogeneity test at the significance test of 5%.Â  The results of the research show that (1) there is a significant difference of effect between the team games tournament learning method and the quantum learning method on the learning achievement in Social Science as indicated by the value of Fcount = 44.399 > that of Ftable = 4.00 at the significance level of 0.05 meaning that the proposed hypothesis is verified; (2) there is a significance difference of effect between the studentsâ high initial ability and the studentsâ low initial ability on the learning achievement in Social Science as shown by the value of Fcount = 28.582 > that of Ftable = 4.00 at the significance level of 0.05 meaning that the proposed hypothesis is verified; and (3) there is a significance interaction effect between the learning methods and the studentsâ initial abilities on the learning achievement in Social Science as pointed out by the value of Fcount = 6.651 > that of Ftable = 4.00 at the significance level of 0.05 meaning that the proposed hypothesis is verified.Based on the results of the research, the teachers should necessarily pay attention to the studentsâ initial abilities in designing the teaching and learning process as this will grow the studentsâ learning motivation, which later improvesÂ  the the learning achievement in Social Science.Â Keywords:Effect, team games tournament learning method, quantum learning method, and learning achievement.